(3GdLGeY aj GdCOhjI GdeaQOIs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s ((3SdjeGf Hf CHj GdHQcGJ Hf CHj fUQ Hf HQcI GHf eQbhT GdjYbhHi GdeSjMi GdeJWHH s)
(3ChdgG (B:s
(3hHYO(B: (3aEfg deG QSe HGdChGeQ GdeWGYI GdYGdjI GdehdhjI GdSdWGfjI GdCYXejI dG RGdJ fGaPI ai GdeZQH hGdeTGQb s
(3BNQgG (B:s
(3RjRahf , GSe (B((3OeTbi dg RGA eaJhMg HYOgG HGHG hSjCJi PcQ GdYfHQG ai MQa GdYjf Ef TGA Gddg s
(3GdeLdO GdChds
(3Edi eGOI (B: (3RjRahfs
(3fSNI QGHYI LjOI hYdjgG ebGHdI HJGQjN (B713(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs